The effects of psychostimulant drugs on blood brain barrier function and neuroinflammation - Sharanya M Kousik; Sharanya M Kousik; T. Celeste eNapier; T. Celeste eNapier; Paul M Carvey; Paul M Carvey; Paul M Carvey (Frontiers Media S.A., 2012)
The blood brain barrier (BBB) is a highly dynamic interface between the central nervous system and periphery. The BBB is comprised of a number of components and is part of the larger neuro(glio)vascular unit. Current literature suggests that psychostimulant drugs of abuse alter the function of the BBB which likely contributes to the neurotoxicities associated with these drugs. In both preclinical and clinical studies, psychostimulants including methamphetamine, MDMA, cocaine, and nicotine, produce BBB dysfunction through alterations in tight junction protein expression and conformation, increased glial activation, increased enzyme activation related to BBB cytoskeleton remodeling, and induction of neuroinflammatory pathways. These detrimental changes lead to increased permeability of the BBB and subsequent vulnerability of the brain to peripheral toxins. In fact, abuse of these psychostimulants, notably methamphetamine and cocaine, has been shown to increase the invasion of peripheral bacteria and viruses into the brain. Much work in this field has focused on the co-morbidity of psychostimulant abuse and human immunodeficiency virus (HIV) infection. As psychostimulants alter BBB permeability, it is likely that this BBB dysfunction results in increased penetration of the HIV virus into the brain thus increasing the risk of and severity of neuroAIDS. This review will provide an overview of the specific changes in components within the BBB associated with psychostimulant abuse as well as the implications of these changes in exacerbating the neuropathology associated with psychostimulant drugs and HIV co-morbidity.